"Be careful what you do": How social threat influences social attention driven by reach-to-grasp movements. Issue 2 (4th March 2022) - Capellini, Roberta; Sacchi, Simona
ABSTRACT: Social attention is the ability to share with social partners the attentional focus on an object and to orient attentional resources after observing others' behaviors. In the present work, we analyzed whether social threat may influence social attention during the observation of social agents' reach-to-grasp movements. In two experimental studies, we adopted a Posner-like paradigm: participants were required to classify neutral stimuli appearing in a congruent or incongruent position with the actor's movement. Membership (ingroup vs. outgroup) and contextual cues (neutral vs. threatening objects) were manipulated. The results showed a robust action-cueing effect: responses to stimuli in a congruent position with the actor's action were faster than responses to incongruent stimuli. Interestingly, we found a stronger effect for the threatening outgroup (i.e., Iraqi) than for the ingroup (i.e., Italian), especially in presence of menacing objects. No effects were found when observing the non-threatening outgroup (i.e., Japanese).